The value of climate-resilient seeds for smallholder adaptation in sub-Saharan Africa - Cacho, Oscar J; Moss, Jonathan; Thornton, Philip K.; Herrero, Mario; Henderson, Benjamin B.; Bodirsky, Benjamin L.; Humpenöder, Florian; Popp, Alexander; Lipper, Leslie (Springer, 2020)
Climate change is threatening food security in many tropical countries, where a large proportion of food is produced by vulnerable smallholder farmers. Interventions are available to offset many of the negative impacts of climate change on agriculture, and they can be tailored to local conditions often through relative modest investments. However, little quantitative information is available to guide investment or policy choices at a time when countries and development agencies are under pressure to implement policies that can help achieve Sustainable Development Goals while coping with climate change. Among smallholder adaptation options, developing seeds resilient to current and future climate shocks expected locally is one of the most important actions available now. In this paper, we used national and local data to estimate the costs of climate change to smallholder farmers in Malawi and Tanzania. We found that the benefits from adopting resilient seeds ranged between 984 million and 2.1 billion USD during 2020–2050. Our analysis demonstrates the benefits of establishing and maintaining a flexible national seed sector with participation by communities in the breeding, delivery, and adoption cycle.